Mimicking Natural Microenvironments: Design of 3D-Aligned Hybrid Scaffold for Dentin Regeneration - Campodoni, Elisabetta; Dozio, Samuele M.; Panseri, Silvia; Montesi, Monica; Tampieri, Anna; Sandri, Monica (Frontiers in Bioengineering and Biotechnology, 2020)
Tooth loss is a common consequence of a huge number of causes and can decrease the quality of humans’ life. Tooth is a complex organ composed of soft connective tissues and mineralized tissues of which dentin is the most voluminous component whose formation is regulated by a very complex process displaying several similarities with osteogenesis. Calcium phosphates, in particular hydroxyapatite (HA), is the phase present in higher amount into the structure of dentin, characterized by microscopic longitudinal dentinal tubules. Following a biomimetic approach, we designed hybrid scaffolds resembling the physico-chemical features of the natural mineralized tissues as an innovative tool for improving regenerative approach in dental applications. The adopted biomineralization process consists in the nucleation of magnesium-doped-hydroxyapatite (MgHA) nanocrystals on the gelatin (Gel) matrix generating hybrid flakes (Gel/MgHA) in which chemical and topotactic constrains assure the formation of a quasi-amorphous MgHA, resembling the chemical and biological features of the natural apatite. The hybrid Gel/MgHA was then merged into the polymeric blend made of chitosan and gelatin to obtain a 3D porous scaffold featured by an aligned structure due to a controlled freeze-drying process. Furthermore, the suitable stability was assured by means of a dehydrothermal cross-linking treatment (DHT), while cell adhesion and proliferation were evaluated by the 3D cells culture in vitro study.